HUBUNGAN USIA IBU DAN BERAT BAYI BARU LAHIR DENGAN RUPTURE PERINEUM - Sugiman, Turiyani (LPPM STIKes Mitra Adiguna, 2024)
Perineal rupture is an injury to the birth canal that occurs during birth due to tissue damage due to pressure on the baby's head and shoulders during the birth process. The aim of the research was to determine the relationship between maternal age and newborn weight with perineal rupture at the Independent Midwife Practice (PMB) Irma Suryani, Prabumulih City in 2023. The research method was analytical, using a cross sectional approach. The population of this study were all mothers giving birth at the Independent Midwife Practice (PMB) Irma Suryani, Prabumulih City. The sample taken in this study used the Random Sampling technique method, namely 149 people. The research instrument is a checklist. The results of the study based on univariate analysis showed that of the 149 respondents there were 64 respondents (43%) who were diagnosed with perineal rupture and 85 respondents (57%) who were diagnosed with not perineal rupture, there were 52 respondents (34.9%) who were of high risk age and 97 respondents (65 .1%) who had a low risk age, there were 35 respondents (23.5%) who had a high risk birth weight and 114 respondents (76.5%) who had a low risk birth weight. Of the 52 respondents with a high risk age, there were 38 respondents (25.5%) who were diagnosed with perineal rupture. Of the 97 respondents who had a low risk age, there were 26 respondents (17.4%) who were diagnosed with perineal rupture and of the 35 respondents who had a heavy newborn baby. At high risk births, there were 31 respondents (20.8%) who were diagnosed with perineal rupture, while of the 114 respondents who had low risk birth weights, there were 33 respondents (22.1%) who were diagnosed with perineal rupture. Conclusion: There is a significant relationship between maternal age and perineal rupture with a P value of 0.000 < ? 0.05 and there is a significant relationship between the weight of the newborn and perineal rupture with a P value of 0.000 < ? 0.05. Keywords : Perineal rupture incidence, maternal age, weight of newborn Bibliography : 18 (2017-2023)